POTENTIALS OF PALUNGAN SALT FARMING IN THE DEVELOPMENT OF CULTURAL TOURISM AND COMMUNITY-BASED EDUCATION IN THE VILLAGE OF TEJAKULA - Widhiarini, Ni Made Ayu Natih; Ariastini, Ni Nengah; Permanita, Ni Putu Feby Devira; Semara, I Made Trisna (Institut Pariwisata dan Bisnis Internasional, 2018)
Palungan salt farming is one of commodity that is still dominated by coastal communities in Tejakula Village. However, since 2010 the number of palungan salt farmers has degraded from 200 farmers to 21 farmers. This resulted in the production of salt manger decreased. On the other hand, salt is one of the foodstuffs needed by various parties for both consumption and industrial needs. Although the Government has issued a policy to empower traditional salt farming through PUGAR, but until now the implementation has not been maximized. The aims of this research is to identify the potential of internal and external physical environments in Tejakula Village to consideration in the effort to conserve local wisdom in synergy with sustainable tourism development. Using the descriptive qualitative research method, Tejakula Village has internal and external potential that is useful to be developed towards the development of living museum as cultural and educational tourism in order to conserve local wisdom and improve the economic level of the community in Tejakula Village.